Implementation of Law No. 23 of 2011 Concerning Zakat Management in LAZISMU and LAZISNU Surakarta - Sekar Ingtyas Garnis Waninghyun Sejati; M. Junaidi; Mutimatun Niami (Universitas Muhammadiyah Surakarta, 2023)
Quality zakat management institutions should be able to manage existing zakat effectively and efficiently, such as LAZISMU and LAZISNU Surakarta as Amil Zakat Institutions that collect and distribute zakat, infaq and shodaqoh. The problem formulation in this research is how to manage and supervise the collection of funds at LAZISMU and LAZISNU Surakarta and how to manage and supervise the distribution of zakat at LAZISMU and LAZISNU Surakarta. So this research aims to describe the management and supervision of zakat carried out at LAZISMU and LAZISNU in Surakarta. The method used is the empirical juridical method using interview techniques and literature study. The results of this research are that various types of collection and distribution are carried out by LAZISMU and LAZISNU Surakarta with their respective Flagship Programs, and there is a supervisory body that carries out supervisory functions over the collection and distribution of zakat, infaq and shodaqoh from external, namely the Ministry of Religion and from Internal in accordance with respective Islamic Community Organizations.